英語コミュニケーションにおける不安軽減のための探索的研究 - Kobayashi Yumi (MEDIA, ENGLISH AND COMMUNICATION, 2024)
This study explored the effect of introducing Global Englishes perspectives into a semester-long course on English communication anxiety. It involved 13 second-year university students using the Japanese version of the Foreign Language Classroom Anxiety Scale (FLCAS) (Yashima et al., 2009); anxiety levels were measured at three intervals. A within-subjects ANOVA revealed that overall anxiety among the students significantly decreased as the course progressed. Furthermore, focus groups and open-ended questionnaires conducted in Japanese were analyzed using in vivo coding and pattern coding. This analysis demonstrated that a deepening understanding of Global Englishes and exposure to diverse English listening experiences reduced students' communication anxiety and enhanced their confidence, leading to a positive perception of their English ("My English"). These findings suggest that integrating Global Englishes perspectives into English education can alleviate student anxiety and enhance confidence, offering valuable insights for educational practices in English language teaching. 本研究では、1 学期間にわたり国際英語論を取り⼊れた授業が、英語コミュニケーションにおける学⽣の不安にどのような変化をもたらすかについての探索的研究を実施した。私⽴⼤学に在籍する 2 年⽣ 13 名の学⽣を対象に、外国語教室不安尺度（FLCAS の⽇本語版）（Yashima et al., 2009）を使⽤し、授業開始時、中間、学期末の 3 時点で不安の度合いを測定。参加者内⼀元要因分散分析を⾏った結果、授業回数を経るごとに学⽣の全体的な不安が有意に減少したことが確認された。さらに、フォーカスグループインタビューと⾃由回答形式の質問紙を⽇本語で実施し、in vivo コーディングとパターンコーディングを⽤いた内容分析を⾏った。この分析から、国際英語論の理解を深め多様な英語のリスニングに触れることが学⽣の英語コミュニケーションに対する不安を軽減し⾃信を⾼め、「My English」に対する肯定的な認識へと繋がることが⽰された。この研究は、英語教育において国際英語論の組み込みが、学⽣の不安を軽減し、⾃信を向上させる可能性があることを⽰唆している。